A Bankruptcy Approach to the Core Cover - Arantza Estévez-Fernández; María Gloria Fiestras-Janeiro; Manuel Alfredo Mosquera; Estela Sánchez- Rodríguez (Tinbergen Institute, 2012)
In this paper we establish a relationship between the core cover of a compromise admissiblegame and the core of a particular bankruptcy game: the core cover of a compromiseadmissible game is, indeed, a translation of the set of coalitional stable allocations capturedby an associated bankruptcy game. Moreover, we analyze the combinatorial complexity ofthe core cover and, consequently, of the core of a compromise stable game.
urn:NBN:nl:ui:31-1871/38470
Keywords: C71; 330; Cooperative game theory; compromise admissible games; bankruptcy; core cover; complexity; Insolvenz; Core; Kooperatives Spiel; Theorie